The Dynamics of Long-Term Care Service Use in Germany - Christine L. Himes; Ulrike Schneider; Douglas A. Wolf (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Population aging and changing family patterns have made elder care an important issue. In 1994, German law-makers enacted a major reform in the country' s long-term care policy, the Dependency Insurance Act (DIA). How, and in what way, will the relative use of formal and informal long-term care services change in response? We address this question using longitudinal data from the German Socio-Economic Panel (GSOEP) to examine the mix of care providers used by older Germans prior to enactment. We find that formal care is more likely to be used by those in the poorest health, the single, or the childless. The presence of daughters increases both the use of family and formal care sources. Future work with more recent waves of the GSOEP is needed to see if family care provision is sustained in an environment of universal public long-term care insurance.
Keywords: 330; Langzeitpflege; Familienpflege; Pflegeversicherung; Familiensoziologie; Alte Menschen; Deutschland